The influence of air and liquid properties on airblast atomization - Rizkalla, A. A. (Cranfield University, 1974)
This thesis reports the results of a detailed programme of research on airblast atomization carried out using a specially designed atomizer in which the liquid is first spread into a thin sheet and then exposed on both sides to high velocity air. The primary aim of the investigation was to examine the influence of air and liquid properties on atomization quality. The work was divided into four main phases:- (1) The first phase was confined to the effects of liquid properties, namely viscosity, surface tension and density on mean drop size. Special liquids were produced to study the separate effect of each property on atomization quality. They presented a range of values of viscosity from 1.0 to 124 centipoise, while surface tension and density were varied between 26 and 73.5 dynes/cm and 0.8 and 1.8 gm/cm3 respectively. Atomizing air velocities covered the range of practical interest to the designers of continuous combustion systems and varied between 60 and 125 m/sec.(2) To obtain experimental data on the influence of air properties, notably air density, on mean drop size, the air temperature was varied between 23 and 151°C at atmospheric pressure in one series of experiments, while a separate study on the effect of air pressure on atomization quality was undertaken, where tests were conducted at constant levels of air velocity and temperature, using a range of liquid flows from 5 to 30 gm/sec, at various levels of air pressure between 1 and 8.5 atm. (3) In order to provide a comprehensive picture of airb1ast atomizer performance over a wide range of conditions the separate effects of varying air velocity, liquid flow rate, and hence atomizing air/liquid mass ratio on SMD were examined. This study enabled a better understanding of the effects of changes in operation on the atomizer's performance. (4) In all three phases above, velotities of both inner and outer atomizing air streams were kept equal. This last phase was aimed at studying the effect of varying the velocity between the inner and outer air streams. Best atomization quality was achieved when 65% of the total atomizing air was flowing through the outer stream. A detailed description of the light-scattering technique for drop size measurement is included. A discussion on the importance of the results obtained and their direct relevance to the design of airblast atomizers is given. A dimensional analysis and inspection of all the data obtained on the effects of air and liquid properties on atomization quality showed that over the following range of conditions: Liquid viscosity 1.0 to 44 centipoise Liquid surface tension 26 to 73.5 dynes/cm Liquid density 0.78 to 1.5 gm/cm³ Air velocity 70 to 125 m/sec Air temperature 20 to 151 °c Air pressure 1.0 to 8.5 kgf/cm² . Air/liquid ratio 2 to 6 Cont..........